Lockdown Impact due to Corona Pandemic on Electric Power Quality and Its Alternative Solutions for a University Office Building - Ida Ayu Vadanti Locana Diwy; Amien Rahardjo; Aji Nur Widyanto; Faiz Husnayain; Rudy Setiabudy (ELKHA : Jurnal Teknik Elektro, 2022)
The pandemic has changed the usage pattern of electrical appliances in buildings. This new pattern can create new problems in terms of power quality and thus affect the electrical system’s reliability. The purpose of this study is to determine the power quality of the Dean Office Building, Faculty of Engineering, Universitas Indonesia, and propose alternative solutions to its problems. To determine the quality of electric power, the related parameters such as voltage, current, power factor, and harmonics are measured first. The measurement results are compared with existing standards. If these standards cannot be met, damage to electrical equipment can occur. Out of eight parameters, three did not meet the criteria. First, overvoltage on average voltage with the range of 231.5-232.8 V. Second, IHDi nominal on the 3rd, 5th, 7th, and 15th harmonics for Thursday, April 7, 2022 on 06:11 with the value of 70.3%, 55.34%, 27.1%, and 8.07%. And third, the minimum power factor for the T phase with the value of 0.7219 is still less than 0.85. Possible solutions include checking and changing the supply transformer tap-changer, making an energy monitoring system and wiring diagram for understanding the load profile of the building, and using a single-tuned filter for harmonic currents.